Cumulation of Sentences in Concurrence of Criminal Offenses (Concursus) under the New Indonesian Criminal Code: Re-Actualization of the Principles of Proportionality and Individualization of Sentencing - Muhammad Ridwan Lubis; Cut Nurita; Diana Lubis; Rini Novita (Jurnal Smart Hukum (JSH), 2027)
The enactment of Law No. 1 of 2023 on the Indonesian Criminal Code (KUHP Baru) marks a fundamental shift in the regulation of concurrence of criminal offenses (concursus), replacing the mixed cumulative-absorption system inherited from the colonial Wetboek van Strafrecht. This study examines the transformation of sentence cumulation in concursus and evaluates the extent to which the new regime re-actualizes proportionality and individualization in sentencing. Employing a normative juridical method with statutory, conceptual, and comparative approaches, the research analyses Articles 123–128 of the new KUHP alongside doctrinal developments and hypothetical case simulations. The findings reveal that the new KUHP explicitly abandons the pure cumulative stelsel in favor of an aggravated absorption system (stelsel absorpsi yang dipertajam), whereby the maximum penalty for multiple acts is set at the most severe principal threat plus one-third, and judicial discretion is bounded by overarching sentencing objectives that mandate proportionality and individual culpability. The discussion demonstrates that this structural change harmonizes Indonesian concursus law with modern sentencing theories, particularly limiting retributive excess and enabling individualized sanctions. However, residual ambiguity in the definition of “multiple acts” and the absence of operational guidelines for aggravation pose risks of disparity. The article concludes that the new KUHP constitutes a significant normative advancement toward proportionality and individualization, but its practical realization demands coherent implementing instruments and intensive judicial training